(untitled) - Anderson, Lucas Steven

Evaluating measurement techniques: establishing a testing framework for residual stress in selective laser melted Ti-6Al-4V (Stellenbosch : Stellenbosch University, 2017)
Thesis (MEng)--Stellenbosch University, 2017.